2021
DOI: 10.1128/aem.02704-20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Phylogenetic Structure in the Dynamics of Coastal Viral Assemblages

Abstract: Marine microbes, including viruses, are an essential part of the marine ecosystem, forming the base of the foodweb and driving biogeochemical cycles. Within this system, the composition of viral assemblages changes markedly with time, with some of these changes being repeatable through time; however, the extent to which these dynamics are reflected within versus among evolutionarily-related groups of viruses is largely unexplored. To examine these dynamics, changes in the composition of two groups of ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Targeted gene sequencing is increasingly being applied to explore spatiotemporal patterns of viral diversity (Adriaenssens & Cowan, 2014;Finke & Suttle, 2019;Frantzen & Holo, 2019;Gustavsen & Suttle, 2021;Howe-Kerr et al, 2022;Y. Li et al, 2018;Montalvo-Proaño et al, 2017;Prodinger et al, 2020;Short et al, 2010;Tong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted gene sequencing is increasingly being applied to explore spatiotemporal patterns of viral diversity (Adriaenssens & Cowan, 2014;Finke & Suttle, 2019;Frantzen & Holo, 2019;Gustavsen & Suttle, 2021;Howe-Kerr et al, 2022;Y. Li et al, 2018;Montalvo-Proaño et al, 2017;Prodinger et al, 2020;Short et al, 2010;Tong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Amplicon sequencing is a targeted, polymerase chain reaction (PCR)-based HTS approach that allows deep characterization of genetic variants within virus populations (Short et al 2010). The targeted nature of amplicon sequencing reduces the economic and computational investment required for spatiotemporal investigations of virus communities at ecologically relevant scales (see Finke & Suttle, 2019;Frantzen & Holo, 2019;Gustavsen & Suttle, 2021;Howe-Kerr et al, 2022;Montalvo-Proaño et al, 2017). The number of studies leveraging virus amplicon sequencing has increased rapidly over the last two decades (e.g., 16 peer-reviewed publications in 1998 compared to 127 in 2021 based on a Web of Science search of 'virus amplicon sequencing', November 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Four monophyletic clades of picorna‐like viruses probably representing at least two new viral families were identified using sequence analysis, showing the potential of a single‐gene survey for RNA viral discovery in marine environments [ 107 ]. In addition to viral discovery, more recent studies based on RdRp‐targeted RT‐PCR also revealed the temporal and spatial variation of picorna‐like ssRNA viruses in the coastal areas of British Columbia by combining location and time‐series sampling [ 108 ], the predominant role of picornavirads in the pool of RNA viruses in tropical coastal seawater samples through additional metagenomic methods [ 109 ], and the impact of RNA viruses on the community composition of the potential host with extra amplicon sequencing of marker genes [ 108 , 110 ]. Notably, these data gave an initial glimpse into the diversity, richness, and ecology of a particular RNA virus group in the ocean, but this method provided little information about genetic diversity (i.e., other viral genes) and is inapplicable to the global and comprehensive assessment of RNA viruses, especially at the genome and function levels, because of underrepresentation of all viral groups and the lack of complete genetic materials.…”
Section: Meta‐omics Of Virus Discovery and Annotationmentioning
confidence: 99%
“…Globally 91.4% of all sequences from ocean microbes are unidentifiable organisms, thus our knowledge is miniscule. Viruses are key players in oceans – they catalyze the cycling of nutrients, and are critical to global biogeochemical cycles ( Gao et al, 2021 ; Gustavsen and Suttle, 2021 ).…”
Section: Plenary Keynote Sessionsmentioning
confidence: 99%